Scanning mutagenesis of the putative transmembrane segments of K(ir)2.1, an inward rectifier potassium channel - Collins, Anthony (National Academy of Sciences, 1997)
Structural models of inward rectifier K(+) channels incorporate four identical or homologous subunits, each of which has two hydrophobic segments (M1 and M2) which are predicted to span the membrane as α helices. Since hydrophobic interactions between proteins and membrane lipids are thought to be generally of a nonspecific nature, we attempted to identify lipid-contacting residues in K(ir)2.1 as those which tolerate mutation to tryptophan, which has a large hydrophobic side chain. Tolerated mutations were defined as those which produced measurable inwardly rectifying currents in Xenopus oocytes. To distinguish between water-accessible positions and positions adjacent to membrane lipids or within the protein interior we also mutated residues in M1 and M2 individually to aspartate, since an amino acid with a charged side chain should not be tolerated at lipid-facing or interior positions, due to the energy cost of burying a charge in a hydrophobic environment. Surprisingly, 17 out of 20 and 17 out of 22 non-tryptophan residues in M1 and M2, respectively, tolerated being mutated to tryptophan. Moreover, aspartate was tolerated at 15 out of 22 and 15 out of 21 non-aspartate M1 and M2 positions respectively. Periodicity in the pattern of tolerated vs. nontolerated mutations consistent with α helices or β strands did not emerge convincingly from these data. We consider the possibility that parts of M1 and M2 may be in contact with water.